Quelle(s) singularité(s) des imaginaires urbains de la fiction climatique au cinéma ? - Pierre‑Jacques Olagnier (ReS Futurae)
The article proposes to question the specificity of the place of urban imaginaries in cli‑fi films. Are these imaginaries radically different from the most common representations of urban spaces in science fiction narratives? The analysis of the still limited place of climate fiction in cinema, followed by an examination of the use of urban representations in a corpus of science fiction films, both within and outside the cinematic narrative, shows that there does not seem to be a radical break between the urban imaginaries of Cli‑Fi and those of science fiction in general.